On the influence of the load sequence on the structural reliability of steel members and frames. (November 2015) - Taras, Andreas; Huemer, Stefan
Abstract: The influence of different load sequences on the deterministic resistance of steel structures (in the inelastic range) is a well-understood phenomenon. However, the impact of different load sequences on the reliability of members and frames made of steel has not been specifically studied in the past. Design rules for the stability and strength checks of such elements and structures are found, e.g., in Eurocode 3[1] . The published background shows that load sequences and amplification patterns were not systematically included in the analysis of the reliability of the design rules for steel structures in Eurocode 3. In this paper, the impact of different load sequences on the reliability of three design rules or procedures (the resistance of plastic cross sections, of beam columns and of portal frame structures) is studied and illustrated by means of representative examples. The results show the significance of the load sequence at the level of scatter and non-exceedance probability of resistances. The paper finally discusses the implications of the study's findings for code-making, as well as the potential of accounting for the load sequence in the reliability assessment of, e.g., existing structures.